(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The problem of coronavirus infection is sweeping the world at lightning speed in 2020. It is because the pandemic has spread across the globe. There is not a single corner of the globe that the virus has not reached. High contagiousness and, consequently, high morbidity and mortality initially affected the world and the entire medical community. Doctors did not know how to treat or what to do. A period of panic started in the public health service of almost all countries. Kazakhstan is no exception. The sad statistics are as follows: as of 31.01.2021, 103 million 213 thousand 392 people were infected. 2,231,154 people died. The mortality rate was 2.16%. We offer to your attention a clinical case of an elderly patient with a confirmed diagnosis of Covid-19 against a background of multimorbid somatic pathology.